Transcriptional control of 2, 4‐dinitrotoluene degradation in Burkholderia sp. R34 bears a regulatory patch that eases pathway evolution. (26th March 2021) - Pérez‐Pantoja, Danilo; Nikel, Pablo I.; Chavarría, Max; de Lorenzo, Víctor
Summary: The dnt pathway of Burkholderia sp . R34 is in the midst of an evolutionary journey from its ancestral, natural substrate (naphthalene) towards a new xenobiotic one [2, 4‐dinitrotoluene (DNT)]. The gene cluster encoding the leading multicomponent ring dioxygenase (DntA) has activity on the old and the new substrate, but it is induced by neither. Instead, the transcriptional factor encoded by the adjacent gene ( dntR ) activates expression of the dnt cluster upon addition of salicylate, one degradation intermediate of the ancestral naphthalene route but not any longer a substrate/product of the evolved DntA enzyme. Fluorescence of cells bearing dntA ‐ gfp fusions revealed that induction of the dnt genes by salicylate was enhanced upon exposure to bona fide DntA substrates, i.e., naphthalene or DNT. Such amplification was dependent on effective dioxygenation of these pathway‐specific head compounds, which thereby fostered expression of the cognate catabolic operon. The phenomenon seems to happen not through direct binding to a cognate transcriptional factor but through the interplay of a non‐specific regulator with a substrate‐specific enzyme. This regulatory scenario may ease transition of complete catabolic operons (i.e. enzymes plus regulatory devices) from one substrate to another without loss of fitness during the evolutionary roadmap between two optimal specificities.